Perwujudan Keadilan Menurut Perspektif Filsafat Hukum Dalam Aspek Perlindungan Korban Kejahatan Di Kerangka Hukum Indonesia - Saria, Matthew (Jurnal Hukum & Pembangunan, 2021)
Human relations have impacts, in terms of crimes that can cause victims to be disadvantaged parties. In practice, bias against the victim is exist if compared with the arrangement concerning the rights of doers whereas the existence of victims are protected by the state law for the sake of justice. The sense of justice must be upheld in a legal framework that is to uphold justice in the reality of society, regulation is only as law if it’s felt fair. Which means that in protecting victims, it is not enough just to punish the perpetrator, the victim aspect must also be seen as an important measure. The application of the principle of justice in the aspect of protecting crime victims is a state responsibility to be upheld, and the fulfillment of the perspective of legal justice within the framework of Indonesian law is important to guarantee the truth and fulfill a sense of justice in society.